Periodized Training in Mice: Comparisons between Constant and Undulating Load Models - de Carvalho, Carlos Dellavechia (2020)
Carvalho CD, Kalva-Filho CA, Milioni F, Loures JP, Serrano VS, Silva ASR, Papoti M. Periodized Training in Mice: Comparisons between Constant and Undulating Load Models. JEPonline 2020;23(4):15-24. The purpose of this study was to compare the effects of undulating (UL) and constant load (CL) training models applied in Swiss mice. Twenty male mice were divided into 3 groups: (a) Control Group [CON; n=6]; (b) Undulating Group [ULG; n=7]; and (c) Constant Load Group [CLG; n=7]. Both training periods lasted 8 wks, 5 d∙wk-1, as prescribed in accordance with maximal speed reached during the incremental test (MaxS). The ULG trained through sessions classified as Endurance 1 (60 min at 40% MaxS), Endurance 2 (30 min at 60% MaxS), Endurance 3 (4 x 5 min at 100% MaxS), and Anaerobic (10 x 1 min at 120% MaxS). All sessions for CLG consisted of a 60-min duration at 60% of MaxS. Both training models induced positive adaptations until the 4th wk of training. However, these adaptations were not maintained during the last 4 wks, declining MaxS in relation to baseline. The CLG was able to accomplish only 69% of proposed training volume. However, the ULG was able to accomplish 94% of the proposed volume. Comparing the reasons for sessions failure, CLG presented higher number of dropouts related to unsatisfactory running (P-value = 0.008) and exhaustion (P-value = 0.001), while the ULG quit the sessions mainly due to injuries (P-value = 0.003). These results demonstrate that independently of the training model used, positive adaptations were induced up to the 4th-wk of training with high intensity sessions producing the larger amount of dropouts due primarily to injuries.